Molecular Mechanisms of Cancer Prevention by Gooseberry (Phyllanthus emblica). (30th June 2022) - Kumar, Gaurav; Madka, Venkateshwar; Pathuri, Gopal; Ganta, Vishal; Rao, Chinthalapally V.
Abstract: Indian gooseberry ( Emblica officinalis Gaertn or Phyllanthus emblica Linn ; family Phyllanthaceae) has a recognized history in Indian traditional medicine (Ayurveda). Various therapeutic properties have been attributed to gooseberry as a dietary supplement. Many parts of the plant (fruits, seed, leaves, root, bark, and flowers) possess various activities and are used to treat a range of diseases. This review focuses on the evidence for the cancer-preventive properties of gooseberry, its extracts, and its principal phytochemicals based on studies In Vitro and In Vivo. Most importantly, in multiple rodent models of cancer, treatment with P. emblica was found to prevent tumor incidence, number, and volume at various organ sites. The mechanism(s) implicated in gooseberry-mediated cancer inhibition are diverse and include antioxidants, Phase I and II enzyme modifications, anti-inflammatory action, regulation of the cell cycle, and modulation of oncogenic signaling genes. Studies in humans also indicate that P. emblica can offer various health benefits and synergize with other treatments. This review provides detailed information on the potential use of gooseberry extract as an anticarcinogenic in humans, illuminates the therapeutic applications, and discusses clinical trials.